FORMULATION AND DEVELOPMENT OF TASTE MASKED SUSPENSION USING ION EXCHANGE RESINS - Dr. Bharat V. Jain (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
In the present work the attempt was made to prepare taste masked suspension of Ambroxol Hydrochloride by abating the intensely bitter taste of Ambroxol Hydrochloride. Taste abatement was done by complexing of Ambroxol hydrochloride with different Ion Exchange Resins (IER) like Tulsion 335 and Indion 214 in different ratios. The prepared suspensions were evaluated for taste, drug content, particle size, viscosity, sedimentation volume and drug release. The resonates prepared with drug- T335 ratio (1:2) at pH 8, gave maximum drug loading. Suspension containing above resinates showed more than 80% In vitro drug release within 30 min. Prepared formulation also showed good stability and can retain its palatable taste. The developed formulation was an additional advantage like simplification of manufacturing procedure and is economical. Thus, the “patient friendly dosage form” of bitter drugs, especially for pediatric, geriatric, bedridden, and noncooperative patients, can be successfully formulated using this technology